Effects of Brewer’s Yeast Supplementation on Growth, Survival and Immune Response in Giant Freshwater Prawn (Macrobrachium rosenbergii) Juvenile - ปิยะธีรธิติวรกุล, สมเกียรติ; เจนธนานันท์ , สุรัตนา (KKU Science Journal, 2012)
Main purpose of this study effects of supplemented Brewer’s yeast (0%, 0.2%, 0.5%, 1% and 2%) on growth, survival and immune responses of Giant Freshwater Prawn (Macrobrachium rosenbergii). All diets were isonitrogenous with protein of 38% and lipid of 8%. Prawns with initial body weight (4.29±0.20 g.) and total length (6.54±0.25 cm.) were randomly sampled to rear in 32x52x30 cm3 glass aquaria (with close recirculation water system) at the stocking rate of 6 prawns per aquarium. They were fed to apparent satiation three times for 16 weeks. The results showed that growth of prawn fed with 1% Brewer’s yeast supplemented diet were significantly (p<0.05) higher than those of other treatments. Immune response before and after challenging the prawn with Vibrio harveyi strain 639 for 4 day showed that total hemocyte count and phenoloxidase activity of the prawn fed with 1% Brewer’s yeast were significantly (p<0.05) higher than those of other treatments. Cumulative mortality of prawn fed with 1% Brewer’s yeast were significantly (p<0.05) lower than those of other treatments. The study concluded that Brewer’s yeast supplemented for 1% in diet was optimum for promoting growth, survival and immune responses in Giant Freshwater Prawn (Macrobrachium rosenbergii).